The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3233/jad-141977
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Aberrant Cell Cycle in Alzheimer’s Disease Lymphocytes: Diagnostic Prospects

Abstract: In Alzheimer's disease (AD), molecular changes are observed not only in patients' neurons but also in peripheral cells, such as blood lymphocytes. These include changes in the level of oxidative stress markers, mitochondria impairment, and aberrant cell cycle regulation in AD blood lymphocytes. While the concepts of early causes of AD are currently highly controversial, these findings provide support for the cell cycle hypothesis of AD pathomechanism and emphasize the systemic nature of the disease. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 186 publications
7
43
0
Order By: Relevance
“…Mitochondria extracted from AD lymphocytes also showed raised levels of protein oxidation markers: 3NT and protein carbonyls, as well as protein-bound HNE, a lipid peroxidation marker. This is in accordance with increased glutathione disulfide levels and lowered plasma levels of glutathione GSH observed in AD lymphocytes [46]. Furthermore, recent data showed that increased susceptibility to oxidative death of lymphocytes from AD patients correlates with dementia severity [50].…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Mitochondria extracted from AD lymphocytes also showed raised levels of protein oxidation markers: 3NT and protein carbonyls, as well as protein-bound HNE, a lipid peroxidation marker. This is in accordance with increased glutathione disulfide levels and lowered plasma levels of glutathione GSH observed in AD lymphocytes [46]. Furthermore, recent data showed that increased susceptibility to oxidative death of lymphocytes from AD patients correlates with dementia severity [50].…”
supporting
confidence: 82%
“…Surprisingly, multiple recent studies suggest that cell cycle proteins' aberrant re-expression and the reentry of the cell cycle may represent a pathological feature of mature AD neurons [52]. Research points out that rather than being a consequence of neurodegeneration, cell cycle re-entry is its cause, and consequently cell cycle regulatory proteins of G1/S phase checkpoint may develop into early AD biomarkers [46,53,54].…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 99%
See 3 more Smart Citations